IMPLEMENTING QUANTUM TEACHING MODEL TO INCREASE STUDENTS’ LEARNING OUTCOMES ON SBDP SUBJECT AT GRADE IVA SD CENDANA RUMBAI - Zaki Alharis; Zufriady; Lazim N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was initiated by the low grade on SBdP subject of students at grade IV A SD Cendana Rumbai. Thus, quantum teaching model was implemented in order to increase the students’ learning outcome on SBdP subject at grade IV A SD Cendana Rumbai. Type of this research was classroom action research involving 20 students of grade IV A, consisting of 10 males and 10 females. The research was conducted in December 2020. The data were collected from the observation sheets and a test. After applying quantum teaching model, the teachers’ activity increased in Cycle I with the percentage from 70,83% to 75%. In Cycle II, the percentage increased from 79,16% to 83,33%. Then, in Cycle III the percentage reached 91,66%. Besides, the students' activity also increased. In Cycle I, the percentage increased from 70,83% to 75%. In Cycle II, the percentage increased from 79,16% to 83,33%. At last, in Cycle III, the percentage reached 91,66% in two meetings. Thus, this research found that the students’ learning outcomes on SBdP subject increased from 76,54 in Cycle I to 77,5 in Cycle II, and to 81,5 in Cycle III. Based on these results, the increase of the percentage was 1,59% in Cycle I, 2,92% in Cycle II, and 8,23% in Cycle III. To sum up, implementing quantum teaching model increased students’ learning outcomes on SBdP subject at grade IV A SD Cendana Rumbai.